2018
DOI: 10.2478/rjim-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in diabetic nephropathy: a cross-sectional study

Abstract: Objective: To investigate the relationship between sarcopenia and diabetic nephropathy. criteria which consist of hand grip strength, 6-meter walking test and muscle mass. Methods Results:The frequency of sarcopenia increased gradually from 15,1% in healthy control group to 21,4% in the diabetes group, and 34% in diabetic nephropathy group (X 2 for trend, p=0.029),. The frequency of sarcopenia was similar in diabetes and diabetic nephropathy group. However, the frequency of sarcopenia was higher in diabetic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…A report from the Korean Sarcopenic Obesity Study, in which sarcopenia was defined using the skeletal muscle index only, found the prevalence of sarcopenia in patients with T2DM is much higher than the controls (15.7% vs. 6.9%) [ 12 ]. Similarly, Çeliker et al [ 28 ] reported a higher prevalence of sarcopenia in T2DM individuals (21.4%) compared with those without T2DM (15.1%) in Turkey. In our study, we reported that the prevalence of sarcopenia in older adults with T2DM was 8.9% (mean 67.6 years).…”
Section: Discussionmentioning
confidence: 85%
“…A report from the Korean Sarcopenic Obesity Study, in which sarcopenia was defined using the skeletal muscle index only, found the prevalence of sarcopenia in patients with T2DM is much higher than the controls (15.7% vs. 6.9%) [ 12 ]. Similarly, Çeliker et al [ 28 ] reported a higher prevalence of sarcopenia in T2DM individuals (21.4%) compared with those without T2DM (15.1%) in Turkey. In our study, we reported that the prevalence of sarcopenia in older adults with T2DM was 8.9% (mean 67.6 years).…”
Section: Discussionmentioning
confidence: 85%
“…Finally, 16 studies ( 14 29 ) were included in the current meta-analysis and systemic review. Among those publications, three ( 14 16 ) mentioned the relationship between HbA1c and sarcopenia, one ( 17 ) mentioned prediabetes, seven ( 18 24 ) mentioned diabetes, and five ( 25 29 ) mentioned diabetes-related complications, ( Figure 1 ). The characteristics of studies included were shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of five studies ( 25 29 ) (n=3286 participants, females: 46.4%) were included. The combined OR of the relationship between diabetes complications and the risk of sarcopenia was 2.09 (95% CI:1.62–2.70, I²=0%, P=0.467).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in study by Celiker et al, frequency of sarcopenia was similar in diabetes and diabetic nephropathy group. 29 In this study the BMI was low in relatively higher number of patients with diabetic nephropathy patients as compared to non-nephropathy. The causative role of either reduced visceral fat or reduced muscle mass is supported by of this finding.…”
Section: Discussionmentioning
confidence: 54%